State-specific Prevalence and Factors Associated With Current Marijuana, ENDS, and Cigarette use Among US Adults With Asthma - Mohammad Ebrahimi Kalan MS, PhD; Zoran Bursac PhD; Rime Jebai MPH; Samane Zare PhD; Wei Li MPH, PhD; Prem Gautam MPH, PhD; Abir Rahman PhD; Kenneth D Ward PhD; Ziyad Ben Taleb MD, PhD (SAGE Publishing, 2022)
Background The use of marijuana (MJ), combustible cigarettes (hereafter cigarettes), and electronic nicotine delivery systems (ENDS) is widespread among United States (US) adults and linked to worsening respiratory symptoms, especially among adults with asthma. This study examined state-specific prevalence and factors associated with MJ, ENDS, and cigarette use among US adults with asthma. Methods We analyzed data of 41 974 adults aged ≥18 years having self-reported current asthma from the 2018 Behavioral Risk Factor Surveillance System (BRFSS). We reported weighted prevalence to account for complex survey design and performed multivariable logistic regression models to examine factors associated with current use of MJ, ENDS, and cigarettes. Results Overall prevalence of current MJ, ENDS, and cigarette use among adults with asthma was 14.5%, 6.6%, and 27.2%, respectively. Our results showed the US states and territories with highest and lowest use prevalence for MJ (California: 23.6% vs Guam: 3.2%), ENDS (Indiana: 12.8% vs North Dakota: 4.0%), and cigarettes (West Virginia: 42.1% vs Guam: 12.3%). Both MJ and ENDS users were more likely to be male, younger, and live in an urban area, but MJ users were more likely and ENDS users less likely to be Non-Hispanic (NH) American Indian/Alaskan Native. Cigarette users were more likely to be older, have at least 1 health condition, and were less likely to be NH Black or Hispanic and college-educated. Conclusion Many US adults with asthma use MJ, ENDS, and cigarettes. Our findings provide insights for clinicians about the urgent need for effective interventions to reduce tobacco and MJ use among adults with asthma.